Професійний імідж сучасного керівника ЗЗСО як управлінська проблема - Блудова, Юлія; Дикань , Т. О. (My University, 2023)
Стаття присвячена дослідженню професійного іміджу сучасного керівника закладів загальної середньої освіти (ЗЗСО) як важливої управлінської проблеми та складової модернізації освітньої системи. Імідж керівника ЗЗСО є регулятором професійної поведінки , а свідома та цілеспрямована робота над ним стає життєво необхідною потребою для реалізації цілей установи в умовах конкуренції. The article is devoted to the study of the professional image of the modern head of general secondary education institutions as an important management problem and a component of the modernization of the educational system. The image of the head of the general secondary education institutions is a regulator of professional behavior, and conscious and purposeful work on it becomes a vital necessity for the implementation of the goals of the institution in competitive conditions.
Keywords: імідж; керівник; управління; ЗЗСО; image; manager; management; ZZSO